Modeling of Functional Dependence Emergent Qualities of Economic Systems - Lazebnyk, Larysa Leonidivna; Nykytchenko, Nataliia Valeriivna; Hurochkina, Viktoriia Viktorivna; Kravchenko, Liudmyla V. (Atlantis Press, 2019)
Multilateral issues of ensuring prosperity country's economic system are the achievement of efficiency and success industrial enterprises in field behavioral aspect's entrepreneurship in emerging economy. Such a direction of research, which is leaked from experimental economy, places emphasis on strategic behavior of entrepreneurs operating in economy emergent type. Emergent responses and manifestations in global economy are both centralized and peripheral, which is also observed in Ukrainian economy. Therefore, for today remains the relevant direction of scientific research of characteristic signs of economic systems, namely new qualities which cannot be predicted, relying only on information concerning components of this system. Authors stewed key components of the emergence of an emerging economy on example of Ukraine that is concentrated in Financial, Social, Management and Innovation blocks. It characterized manifestations of emergence properties and it specified priority directions of development an economic system. Interconnection of innovations and emergence economic system is revealed that concentrates attention to the level of implementation emergent qualities of economic system that is characterized on ratio (relation) of innovation activity to the emergence. Article proposes a scientific and methodical approach to construction an economic model functioning of industrial enterprises, their mergers, unions and / or types their economic activity in conditions an emergence economy, which elements of system and their functional dependence are specified, stages formation emergent economic system are indicated.
Keywords: еmergence еconomics; economy emergence type; еconomic security; industrial enterprises; economic modeling